Range extension of the Mexican-endemic killifish Profundulus chimalapensis (Cyprinodontiformes: Profundulidae), with comments on its phylogenetic placement and possible intergeneric hybridization with Tlaloc Álvarez & Carranza 1951 - Arroyave, Jairo; Hernández-Ávila, Sonia Gabriela; Matus-Martínez, Manuel; Matamoros, Wilfredo A. (Zootaxa, 2024)
Recent ichthyological surveys in southern Mexico resulted in the unexpected discovery of populations of P. chimalapensis outside its distribution range, broadening its extent of occurrence to a total of three river basins (Coatzacoalcos [original], Grijalva, Ostuta) and two versants (Atlantic [original] and Pacific). The taxonomic nature of these populations was further investigated using comparative genetic data in a phylogenetic framework. Our results include the first assessment of the phylogenetic position of P. chimalapensis with respect to other Profundulus species and imply a sister-group relationship with P. oaxacae. Remarkably, our results also imply a close phylogenetic affinity of some P. chimalapensis samples with the genus Tlaloc, which we interpret as possible evidence of intergeneric hybridization, a phenomenon previously unreported in the family. If our interpretation in this regard is correct, it raises several broader evolutionary and taxonomic questions, such as the role that introgressive hybridization might be playing as a driver of speciation in profundulid fishes. From a historical biogeographic perspective, the proposed expanded geographic range could be explained by inter-basin dispersal enabled by recent or historical events (e.g., paleodrainage connections, headwaters stream capture, floodings) in the same fashion as these have been invoked to explain distribution patterns in other Middle American freshwater fishes.